Successfully Treated Norovirus- and Sapovirus-Associated Diarrhea in Three Renal Transplant Patients - Noha Ghusson; Gustavo Vasquez (Case Reports in Infectious Diseases)
Objectives. To examine the burden of norovirus- and sapovirus-related diarrhea in renal transplant patients and to propose the use of nitazoxanide as a therapeutic option for treatment. Methods. We reviewed three renal transplant patients with viral diarrhea requiring hospitalization due to acute renal failure and signs of graft rejection. All three patients were treated with nitazoxanide. We examined their clinical courses after therapy and compared time to resolution of symptoms and viral shedding. Results. In all three renal transplant patients, improvement of diarrheal illness was witnessed within one week of nitazoxanide initiation. Conclusions. Infectious diarrhea remains an underestimated yet significant cause of morbidity in solid organ transplant patients. Norovirus and sapovirus are often responsible for this presentation. Nitazoxanide was used as a treatment modality with success in reduction of symptoms, decreased duration of illness, and cessation of viral shedding.